Decentering increases approach motivation among distressed individuals. (1st December 2017) - Eftekhari, Eldar; Tran, Alex; McGregor, Ian
Abstract: Decentering is the process of observing one's thoughts from a self-distanced (i.e. third-person) and non-judgmental perspective, and it is clinically known for its anxiolytic and anti-depressive effects. However there is only preliminary evidence relating decentering to improved motivation, and no studies have controlled for changes in affect which can obscure the measurement of motivation (Harmon-Jones, Harmon-Jones, & Price, 2013). In the current investigation, two experiments tested the hypothesis that decentering increases approach motivation, a buoyant state characterized by goal pursuit, independently of changes in affect. In Study 1 ( N = 148), decentering was induced using a self-distancing manipulation (i.e. fly-on-the-wall; Kross & Ayduk, 2011), and in Study 2 ( N = 143) decentering was induced using brief instructions on applying non-judgmental awareness of thoughts. Following previous research showing that decentering is most effective against negative emotional reactivity for distressed people (Kross & Ayduk, 2009), our hypothesis focused on high trait distress participants. Trait distress was operationalized as the average of standardized distress-related scales (e.g. rumination, depression, uncertainty aversion), and state affect was operationalized using the Felt Uncertainty Scale and the PANAS. Analyses revealed that decentering increased self-reported approach motivation for high trait distress individuals, and that this effect was not mediated by changes in state affect. Highlights: Among distressed participants, decentering increases levels of approach motivation. Decentering's effects on approach motivation are independent of changes in affect. Possible mechanism involves reduced aversiveness of negative mental events.